MODERN RESEARCH IN HIGH QUALITY SPORT - Petar Karadžić; Nela Tatar (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Sports science represents a multidisciplinary field that deals with understanding and improving of sports performance. It can be considered like scientific process whose main goal is to point out the practice of sport to improvement of sports performance. The subject of this paper is a practicing technology of development and improvement of strength as one of the primary skills of athletes. The problem of paper is defining of the methods of power development and to determination of its significance in relation to the tasks in a particular sports discipline and accordingly with that determine the appropriate method for developing of strength. The work is designed in the way that in the first part explaining to reader the basic features required building strength, after which the work emphasized the definitions and forms of manifestation of power and also methodical rules in strength training.